Corpora in Language Learning, Translation and Research: Proceedings of the International Conference Corpora in Language Learning, Translation and Research held at the University of Zadar (August 23–24, 2023) (Morepress Books, 2025)
In the realm of modern linguistic studies, corpora play a foundational role that extends across diverse disciplines and applications. These extensive language resources are not merely repositories of linguistic data but serve as indispensable tools for language learners, translators, and researchers alike. The articles compiled in this conference proceedings delve into interconnected themes such as corpora, AI technologies, language education, and cultural translation. Together, they celebrate the dynamic synergy between language, technology, and culture in modern linguistic research. Corpus-driven studies shed light on language use and cultural expressions, revealing how languages adapt within diverse cultural contexts. The task of cultural translation highlights the complexities of conveying cultural nuances across languages and cultures. By exploring language corpora, educators can leverage innovative strategies to enhance language proficiency among learners, thus influencing language pedagogy and curriculum design, and individuals can gain deeper insights into language structure, usage variations, and cultural expressions. Through an exploration of the development and utilization of both general and specialized corpora, the selected collection of articles seeks to enrich our understanding of language and its multifaceted dimensions in today’s rapidly evolving global context.